"You don't know what you are saying 'Yes' and what you are saying 'No' to": hospital experiences of older people from minority ethnic communities. Issue 1 (26th September 2014) - ELLINS, JO; GLASBY, JON
ABSTRACT: Improving responsiveness to the needs of older people from minority ethnic communities has been emphasised as a goal in England since the publication of the National Service Framework for Older People in 2001. Despite this, people from minority ethnic groups consistently give poorer ratings of their health services than 'majority' populations, both in England and across many other health-care systems. Language barriers have been shown to play a particularly important role, and appear to be a stronger predictor of perceived quality of care than ethnic origin per se . This paper reports findings from a larger study exploring older people's experiences of care transitions, focusing on the findings from one case study area which explored the hospital and discharge experiences of older people from minority ethnic communities. A participatory approach was adopted, with older people from the local area collaborating in the design, delivery and analysis of the research as 'co-researchers'. Twenty-four in-depth narrative interviews were carried out with people who had experienced a recent hospital stay as a patient or a family member providing care and support. Our findings show that many aspects of the hospital experience, including the desire for personalised and humanistic approaches to care, are important to older people irrespective of ethnic background. However, older people from minority ethnic communities can also face language and cultural barriers which negatively affect the quality and experience of care. People who had limited English proficiency struggled to understand, communicate and participate in their care. Where professional services were not available or requested, interpreting was provided informally by other patients, family members, hospital staff in clinical and domestic roles, or not at all. We conclude that targeted strategies are required to ensure appropriate and effective hospital services for a multicultural population.